Microscopic extraovarian sex cord proliferations: an undescribed phenomenon. Issue 4 (22nd December 2014) - McCluggage, W Glenn; Stewart, Colin J R; Iacobelli, Jean; Soma, Anita; Cho, Kathleen R; Heatley, Mark K; Boyde, Adam; Clarke, Blaise A
<x xml:space="preserve">Abstract</x> Aims To report a previously undescribed phenomenon of incidentally detected microscopic proliferations of sex cord cells, often mimicking adult granulosa cell tumour or sex cord tumour with annular tubules, in extraovarian locations. Methods and results The six cases were in patients aged 23–58 years. The proliferations were located in the fallopian tube in three cases, and in paraovarian connective tissues, the pelvic side wall, and appendiceal serosa (one case each). Microscopically, they were typically composed of well‐demarcated nests of regular cells with round/ovoid vesicular nuclei, some containing grooves. Microfollicular and/or cribriform arrangements were present in three cases. In five cases, the sex cord lineage was confirmed by positive staining with inhibin and/or calretinin and other sex cord markers. FOXL2 mutation analysis was performed in one case, but was inconclusive. Bilateral oophorectomies and bilateral cystectomies were performed in three cases and one case respectively; there was no sex cord–stromal neoplasm in the removed ovaries. In the two cases in which the ovaries were not removed, imaging showed no suspicious features. Follow‐up in four cases (11 months–6 years) has been uneventful. Conclusions The pathogenesis of these microscopic extraovarian sex cord proliferations is unknown, but they may represent non‐neoplastic proliferations of embryonic remnants.